2007
DOI: 10.1037/1064-1297.15.6.569
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole: Effectiveness and safety under naturalistic conditions.

Abstract: A retrospective study was conducted to examine aripiprazole's effectiveness and safety in a naturalistic treatment setting in both inpatients and outpatients affected by schizophrenia and other psychotic disorders. All patients with schizophrenia, schizoaffective and delusional disorders, and schizoid and schizotypal personality disorders treated with aripiprazole from March 1, 2005, to March 1, 2006, in the authors' community mental health service were divided into outpatient (n=26) and inpatient (n=17) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Most of the studies were prospective double-blind, placebo-controlled trials, 46 56 and all publications reported single-center results. We also identified one double-blind, treatment-controlled trial; 57 one single-blind, placebo-controlled trial; 58 four open-label trials; 59 62 one retrospective study; 63 and four case reports. 64 67 Please see Table 2A, B and Supplementary Table 3 and 4 for further study details and level of evidence (LoE) grading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies were prospective double-blind, placebo-controlled trials, 46 56 and all publications reported single-center results. We also identified one double-blind, treatment-controlled trial; 57 one single-blind, placebo-controlled trial; 58 four open-label trials; 59 62 one retrospective study; 63 and four case reports. 64 67 Please see Table 2A, B and Supplementary Table 3 and 4 for further study details and level of evidence (LoE) grading.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 16 individual drug treatments were studied. The most frequently studied drug was risperidone, 50 , 53 , 54 , 62 and the most frequently studied class of drugs were the antipsychotics, 47 , 48 , 50 , 53 , 54 , 57 60 , 62 , 63 , 66 followed by the antidepressants. 46 , 61 , 64 , 65 Six studies tested other neuroactive drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study suggest that chronic ARI administration may reduce the risk of supersensitivity psychosis, which might be related to a lower rate of rehospitalization. Although a transient worsening of psychosis can appear in certain supersensitized patients due to relatively excessive agonistic effects,32 ARI may be a helpful agent for patients with treatment-resistant schizophrenia by reducing excessive sensitivity to dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…As an adverse event it is not reported in the dataset and on the contrary, aripiprazole is a recommended evidence based treatment against agitation associated with schizophrenia or bipolar mania (Sanford and Scott, 2008; Gonzalez et al, 2013; Citrome et al, 2016). However, it has been reported under naturalistic conditions (Di Lorenzo et al, 2007) and especially in vulnerable populations such as elderly patients (Coley et al, 2009). Agitation has also been described when initiating aripiprazole in patients after prolonged treatment with potent D2 blocking agents that may result in an upregulation of postsynaptic dopamine receptors (Lea et al, 2007).…”
Section: Efficacy Datamentioning
confidence: 99%